Efficiency analysis of Mexican Lazaro Cardenas port - Ameŕica I. Zamora-Torres; Cinthya Cobian (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: The port administration is an important regulator of international trade operations, as well as a facilitator and accelerator of trade. Hence, it's important to detect the factors that must be improved to achieve greater efficiency. Therefore, the aim of this research is to determine the level of efficiency of the port system of Lazaro Cárdenas in the period 2010-2017. Methodology: This paper develops a simulation model based on operations research, which consists in finding the optimal gantry crane assignment to improve the efficiency of the terminal, through the design of algorithms to the port subsystems services operation and analyses the effect of infrastructure and process improvements on gate congestion. Findings: The results show that the period under analysis was inefficient. These point out the necessity of better operational strategies for the Lazaro Cárdenas port. The results also indicate that the introduction of an appointment system can reduce the average turnaround times. Originality: This paper provide new knowledge that can be used as a new approaches to solve efficiency problems at Lazaro Cardenas port, and also the algorithm created for this analysis could be used in several ports to measure their efficiency as well.
urn:nbn:de:gbv:830-882.054867; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Logistics; Port; Efficiency; Operational research